2017
DOI: 10.5194/hess-21-1397-2017
|View full text |Cite
|
Sign up to set email alerts
|

The European 2015 drought from a climatological perspective

Abstract: Abstract. The summer drought of 2015 affected a large portion of continental Europe and was one of the most severe droughts in the region since summer 2003. The summer of 2015 was characterized by exceptionally high temperatures in many parts of central and eastern Europe, with daily maximum temperatures 2 °C higher than the seasonal mean (1971–2000) over most of western Europe, and more than 3 °C higher in the east. It was the hottest and climatologically driest summer over the 1950–2015 study period for an a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
210
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 262 publications
(256 citation statements)
references
References 57 publications
12
210
0
Order By: Relevance
“…Analysed period: 1876-2012 [Colour figure can be viewed at wileyonlinelibrary.com] values correspond to negative SST anomalies over the Mediterranean Sea and the Black Sea and positive SST anomalies over the Atlantic Ocean (Figure 7f). Overall, the structure of the SST anomalies in Figure 7 resembles the SST anomalies responsible for the occurrence of extreme drought events over the southern and eastern part of Europe (e.g., 2003, 2015) (Van Lanen et al, 2016Ionita et al, 2017). In a recent paper, Ionita et al (2017) shown that warm Mediterranean SSTs have preceded and occurred concurrently with dry summers over most of the central and eastern part of Europe.…”
Section: Large-scale Atmospheric Circulationsupporting
confidence: 84%
See 1 more Smart Citation
“…Analysed period: 1876-2012 [Colour figure can be viewed at wileyonlinelibrary.com] values correspond to negative SST anomalies over the Mediterranean Sea and the Black Sea and positive SST anomalies over the Atlantic Ocean (Figure 7f). Overall, the structure of the SST anomalies in Figure 7 resembles the SST anomalies responsible for the occurrence of extreme drought events over the southern and eastern part of Europe (e.g., 2003, 2015) (Van Lanen et al, 2016Ionita et al, 2017). In a recent paper, Ionita et al (2017) shown that warm Mediterranean SSTs have preceded and occurred concurrently with dry summers over most of the central and eastern part of Europe.…”
Section: Large-scale Atmospheric Circulationsupporting
confidence: 84%
“…Significant and stationary spatial correlations were found between δ 18 O and CI and SPEI3 at European level (Figures 4 and 5). In Figure 7c,f, we further examined the relationship between δ 18 O and oceanic conditions, because the occurrence of droughts and heat waves over the European region is significantly affected by adjacent oceanic condition on yearly to decadal time scales (Cassou et al, 2005 (Feudale and Shukla, 2011;Ionita et al, 2012Ionita et al, , 2017Kingston et al, 2013;Ionita, 2015). Following this line, significant correlations between δ 18 O values and North Atlantic Ocean SST indicate possible connections between the moisture availability over the eastern part of Europe and remote ocean areas.…”
Section: Large-scale Atmospheric Circulationmentioning
confidence: 96%
“…Several studies investigated the atmospheric drivers of individual extreme drought events in Europe. Ionita et al (2017) analyzed the severe JJA drought of 2015 Van Lanen et al, 2016), finding that this event was triggered and enhanced by four heat waves caused by persistent blocking events and a deflection of the Atlantic storm tracks toward the North. Similarly, the extreme precipitation deficits of the Iberian drought in /2005(García-Herrera et al, 2007 and the devastating JJA drought of 2003 (Black et al, 2004) were caused by anticyclonic circulation in combination with a positive soil moisture-precipitation feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Vb cyclogenesis is strongly linked to the upper level atmospheric dynamics interacting with major orography in a low-level baroclinic environment in the WM (e.g., Maheras et al, 2002;Trigo et al, 2002). The increase of WM sea surface temperatures of about +1°C after 1990 (Ionita et al, 2017;their Figure 10d) appears as a plausible explanation for a sustained Vb cyclone occurrence rate. 2.…”
Section: Discussionmentioning
confidence: 99%